Building ‘a mental health - friendly workplace’: Employer’s cost effective investment - Mat Zin, Nora (International Islamic University Malaysia, 2017)
Health and safety in the workplace mainly considers physical, biological, chemical and ergonomic issues as their top priorities. Workplace mental health is often neglected in the overall wellbeing of a person although people spend most of their time in their workplace. Hence, the healthy workplace vision in the organization should encompass a mental healthy workplace vision too to mitigate the economic impact to the organization. The estimated annual cost for mental health issues in the United States is 2.5 trillion US dollars and the number is expected to climb up to 6 trillion US dollars by 2030. In Europe, the cost of work related depression was €617 billion a year.